Dynamics of prevalence of affective disorders in patients with dementia during the COVID-19 pandemic - Rakhman Людмила; Dzis Мирослава (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is devoted to the dynamics of prevalence of affective disorders in patients with dementia during the COVID-19 pandemic.